Respiratory Kinematics During Vocalization and Nonspeech Respiration in Children From 9 to 48 Months. - Connaghan, Kathryn P.; Moore, Christopher A.; Higashakawa, Masahiko (Journal of Speech, Language & Hearing Research, 2004)
The development of respiratory drive for vocalization was studied by observing chest wall kinematics longitudinally in 4 typically developing children from the age of 9 to 48 months. Measurements of the relative contribution of rib cage and abdominal movement during vocalization (i.e., babbling and true words) and rest breathing were obtained every 3 months using respiratory plethysmography (RespitraceTM). Extending earlier findings in 15-month-olds, 2 methods of analysis of rib cage and abdominal movement were used: (a) a dynamic index of the strength of coupling between the rib cage and abdomen, and (b) a classification scheme describing the moment-by-moment changes in each of the 2 components (C. A. Moore, T. J. Caulfield, & J. R. Green, 2001). The developmental course of relative chest wall kinematics differed between vocalization and rest breathing. The coupling of rib cage and abdomen during vocalization weakened significantly with development, whereas it remained consistently strong for rest breathing throughout the observed period. The developmental changes in frequency of occurrence of relative moment-by-moment changes varied across movement type. The results support previous findings that speech breathing is distinct from rest breathing based on the relative contributions of the rib cage and abdomen. Longitudinal changes are likely responsive to anatomic development, including changes to rib cage shape and compliance. Reprinted by permission of the publisher.